KESALAHAN PENERJEMAHAN TEKS BAHASA INDONESIA KE BAHASA ARAB MELALUI GOOGLE TRANSLATE (STUDI ANALISIS SINTAKSIS) (Universitas Negeri Semarang, 2012)
A rendering (translation) today not only can be done by humans but also by machines translator. Beginning with the birth of dictionary software with translation capabilities are limited to words and phrases, has now sprung machines translator who claims not only to translate phrases, sentences and paragraphs, but even complete manuscripts and books. The one that gets a lot of attention is a free online translation service Google Translate various languages ​​which also supports the Indonesian translation. But the extent to which the accuracy of the translation of Google Translate, Google Translate is feasible to use the texts to translate Indonesian to be translated into Arabic. This study aims to determine the accuracy of google translate in the process of translating texts into Arabic Indonesian and describe the errors that dominate the object of study investigators. This study is expected to provide benefits to the students of the Arabic language in order to minimize the use of google translate and considering the translation results, especially in terms of the structure of the grammar.